Effect of heterogeneity of subjects of industrial irradiation processes on spatial distributions of absorbed doses upon electron beam, X-ray and gamma irradiation - Dyuldya, S.V.; Bratchenko, M.I. (Вопросы атомной науки и техники, 2007)
By means of Monte Carlo computer modeling the effects of heterogeneity and spatial arrangement of irradiated disposable syringes on the absorbed dose deposition profiles has been studied for different kinds of irradiation. Substantial deviations from the predictions of conventional approximation of homogenized medium have been found for electron beam irradiation. The dependencies of irradiation process parameters on the orientation and the regularity/stochasticity of the product loading pattern, the variations of dose accumulation in component parts of a syringe and the non-equilibrium dose effects on the internal surface of a syringe needle have been investigated. Шляхом моделювання методом Монте-Карло вивчено вплив гетерогенності та просторового розташування одноразових шприців під опроміненням на профілі поглиненої дози за різних видів опромінення. Для електронного опромінювання знайдені суттєві відхилення від передбачень звичайного наближення гомогенізованого середовища. Виявлені залежності технологічних параметрів опромінювання від орієнтації та регулярності/стохастичності розташування шприців під опроміненням, різниці в накопиченні дози у різних деталях шприцу та нерівноважні дозові ефекти на внутрішній поверхні його голки. Путем моделирования методом Монте-Карло изучено влияние гетерогенности и пространственного размещения облучаемых одноразовых шприцов на профили поглощенной дозы при различных видах облучения. Для электронного облучения обнаружены существенные отклонения от предсказаний обычного приближения гомогенизированной среды. Выявлены зависимости технологических параметров облучения от ориентации и регулярности/стохастичности расположения шприцов под облучением, различия в накоплении дозы в различных деталях шприца и неравновесные дозовые эффекты на внутренней поверхности его иглы.